ANALYSIS OF MECHANICAL STRENGTH OF CONNECTION BETWEEN COMPOSITE AND ALUMINUM SHEET METAL USING HOLE CLINCHING PROCESS - Hardiyantie, Ravenskya Hana; Rahendra P, Lazuardy (Vortex, 2021)
Aluminum and composite materials are the types of materials that are used to construct structures on aircraft airframes. It is not uncommon for both types of materials to be used together with the joining method. In the process of connecting between two types of material in the aircraft structure, it is mostly carried out by the riveting method. This process is carried out by making a hole in the two materials according to the rivet diameter and then the hole diameter is then filled with rivets and the riveting process is carried out. The process uses rivets so that it will relatively increase the weight of the structure because there is additional rivet material. In this study, the objectives are to determine the mechanical strength of the joint between the composite and aluminum sheet metal using the mechanical clinching and riveting processes. The method used is an experimental method, namely by making test specimens with composite and aluminum, solid rivet type fasteners and punches to determine the connection of the riveting, the drilling process is carried out with a hole diameter of 3.5 mm, for the clinching method with variations in the diameter of the punch 3.5 mm, 4.0 mm. , and 4.5 mm. Then the tensile test, macro photo test were carried out. The results obtained from this research are that the maximum load increase in the specimen tested by clinching is because the damage length (gap) value is obtained at the joint boundary between the rivet and the test material.